مجمع محاكم في جنين - شيب نعيرات (My University, 2024)
The project is a complex of three courts, namely the Magistrate's Court, the First Instance and the Court of Appeal, due to the absence of a court of appeal in the northern governorates, and therefore its presence meets the needs of these governorates. The location of the project was chosen in the western part of Jenin, almost in the center of the country, due to the proximity of this area to buildings, government institutions, commercial complexes and city taxi complexes, so its presence in this area facilitates access to the building and also close to the police station and the district. In the design of the building, I relied on rectangular blocks because the rectangle expresses stability and strength, thus giving a sense of control and equality, which is the best form suitable for courts, as well as using glass spaces strongly to express transparency and clarity of the law and that it is visible to all. The building consists of three separate blocks and there is a courtyard in each block, the main block is in the middle and contains the courtrooms, where they were arranged on the first floor of reconciliation and the second beginning and finally the appeal and the ground where the Public Prosecution is located, as for the other two blocks, they contain the offices of judges and other services of the court such as pens and also lawyers' suites